OPTIMALISASI BANK SYARI’AH MENUJU GOOD CORPORATE GOVERNANCE - Fahrur Ulum Fahrur Ulum (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2011)
Abstract: Syarî’ah banking must be optimized earnestly to fulfill the stakeholders interest. The effective implementation of cooporate governance would realize the goal of fairness, accountability, and transparancy.  There are several prior focus of this system manager: basic concept and problems of cooperate governance in syarî’ah banking, the pillars of implementation, and the mechanism.  As a result, to create an effective  cooperate governance of syariah banking, the following aspects must be urgently required: a contract clarity, market discipline, moral dimension, socio-political atmosphere,  law enforcement, and institution. Board of directors, senior management, stockholders, and depositors have important roles to establish the  harmony of syariah banking development. The stakeholders  are directly connected to the mechanism of cooperate governance of syariah banking. Key Words: corporate governance, bank syari’ah, stakeholders, dan mudlârabah